MEDIA POHON ANGKA DAN PENGGUNAANYA DALAM PEMBELAJARAN ASPEK KOGNITIF ANAK USIA DINI - Laksana, Dek Ngurah Laba; Maku, Karmelia Rosfinda Meo; Nuwa, Gaudensia Nio; Sanda, Eusabia (Universitas Muria Kudus, 2024)
The purpose of this developmental research is to create a number tree learning media for the cognitive aspect of recognizing and naming numbers or numerical symbols in Ade Irma Kindergarden. Additionally, this study aims to assess the feasibility of using the number tree learning media and obtain feedback on its usage from teachers at Ade Irma Kindergarden and the course instructor. The research method uses descriptive qualitative methods with data collection techniques through observation, interviews and documentation. The research subjects were children aged 4-6 years.The research results, especially from the aspect of cognitive development, show development that is in line with expectations. Based on the results of research and validation by experts, the number tree media developed in this research is very suitable for use in learning cognitive aspects of early childhood. These findings support the importance of developing contextual learning media that suit the needs and characteristics of young children. It is hoped that the implementation of number tree media can improve the quality of learning at Ade Irma Mataloko Kindergarten and provide a model for the development of learning media in other places.